40Ar/39Ar and U-Pb mineral ages from the Brookville Gneiss: implications for terrane analysis and evolution of Avalonian "basement" in southern New Brunswick - Dallmeyer, R.; Doig, R.; Nance, R.; Murphy, J. (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 1990)
New 40Ar/"Ar hornblende and U-Pb zircon data from units previously thought to represent basement to the Avalon composite terrane in southern New Brunswick yield latest Precambrian or early Cambrian metamorphic cooling ages and a late Precambrian protolith age. Hornblendes from the Brookville Gneiss and from an intrusive amphibolite body within the gneiss yield 40Ar/"Ar isotope correlation ages of 542 ± 4 and 338 ± 2 Ma, respectively. These ages are interpreted to date post-amphibolite facies metamorphic cooling. Euhedral zircons from the Point Pleasant orthogneiss, a quartz dioritic gneiss previously interpreted to be the oldest component of the Brookville Gneiss, show slight inheritance and yield 247Pb/206Pb ages ranging from 603 to 631 Ma. The youngest of these is interpreted to be a maximum age for the orthogneiss protolith. These results, together with other recent U-Pb age data, conflict with previous interpretations of the Brookville Gneiss and the metasedimentary Green Head Group with which it is associated, as a mobilized Proterozoic basement-cover succession upon which an Avalonian ensialic arc developed at c. 600-633 Ma. Instead, the age of the orthogneiss matches that of the arc, and the orthogneiss protolith is likely to have been originally intrusive into the Green Head Group. Although the arc succession is unaffected by high-grade metamorphism, the metamorphic cooling age recorded in the "basement" closely follows evidence of within-arc extension at c. 330 Ma. Hence, the arc/"basement" contrasts in tectonothermal regime could be those of varying structural level within the Avalonian arc rather than requiring the proposed existence of entirely separate terranes.